Utilitarianism approach in ethical decision making among Malaysian social entrepreneurs - Mhd. Sarif, Suhaimi (2013)
Utilitarianism approach in ethical decision making emphasizes on the great consequences of the decision outcomes to the majority of the stakeholders. This is part of the ethical and social responsibilities of entrepreneurs. The utilitarianism ethical conscience reminds entrepreneurs to make trustworthy and profitable entrepreneurship decisions that are acceptable by the stakeholders. The study used personal interview technique with open ended interview questions to obtain the views of 20 entrepreneurs regarding the practice of utilitarianism approach in ethics and social responsibility. The findings showed that one thirds of the entrepreneurs perceived that the practice of utilitarianism approach in ethics and social responsibility is acceptable as a concept or thought, but in practice it is almost impossible due to the strong influence of external factors. The study proposed that future research to use personal interview and self administered survey with more small business owners from other major cities.